PENGARUH TEKNIK RELAKSASI BENSON TERHADAP TINGKAT ANSIETAS PASIEN PRE OPERASI LAPARATOMI (STIKES Telogorejo Semarang, 2024)
Surgery can cause physiological and psychological stress reactions in the form of anxiety that need to be handled. Anxiety management strategies can be done with non-pharmacological treatment, one of which is Benson Relaxation, where this relaxation is a combination of relaxation and the beliefs held by the patient. The purpose of this study was to determine the effect of Benson's relaxation on the level of anxiety in pre-laparotomy patients. This type of research is a quantitative research with a research design using a quasi-experimental method with a pre-test and post-test design with a control group. In collecting data using the Rating Numeric scale of Anxiety (NRS-A) questionnaire. The number of samples in this study were 68 respondents with 34 respondents in the intervention group and 34 respondents in the control group. The sampling technique used was purposive sampling. The statistical tests used were the Wilcoxon Rank Test and the Mann Whitney test. The results showed that there was a significant effect between the Benson Relaxation technique on the anxiety level of pre-laparotomy patients with a p value of 0.000 (p<0.05). Clinical nurses can apply the Benson Relaxation technique in the management of anxiety in pre-laparotomy patients. For further researchers, it can be compared with other therapies in order to get an efficient form of implementation.